Modern Poetry and Artificial Intelligence Investigating How Al-Generated Poetry is Shaping Perceptions of Creativity and Authorship (المجلة الدولية للبحوث العلمية, 2025)
The creative possibilities and constraints of artificial intelligence in poetry generation are examined in this study, with an emphasis on how AI questions conventional ideas of authorship, creativity, and emotional expression. Three different poems, as well as an original thematic poem, were produced using ChatGPT-4 using thoughtfully crafted prompts that drew inspiration from the writings of Pablo Neruda and E.E. Cummings. Each poem was subjected to a thorough self-analysis that looked at thematic depth, literary devices, stylistic choices, and the degree to which AI can replicate human voice and emotion. While recognizing important limitations like the lack of lived experience, cultural context, and emotional authenticity in AI-generated content, the study also discusses graphological aspects and the point of view used in the poems. By providing insights into how machine -generated literature is changing our perception of literary authorship, the findings add to the continuing discussion about artificial intelligence and the creative arts. This study concludes that although AI cannot fully replace human creativity, it does offer significant chances for artistic expression and teamwork.